2019
DOI: 10.3389/fphar.2019.01134
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Patchouli Alcohol Against High-Fat Diet Induced Hepatic Steatosis by Alleviating Endoplasmic Reticulum Stress and Regulating VLDL Metabolism in Rats

Abstract: Nonalcoholic fatty liver disease (NAFLD) is currently the most common chronic hepatic disorder worldwide. The earliest stage of NAFLD is simple steatosis, which is characterized by the accumulation of triglycerides in hepatocytes. Inhibition of steatosis is a potential treatment for NAFLD. Patchouli alcohol (PA) is an active component of Pogostemon cablin (Blanco) Benth. (Labiatae), which is a medicinal food in Asia countries and proved to possess hepatoprotective effect. This research aimed to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…46 It has been veried that the action of PERK could affect VLDL receptors that are regulators of liver TG and fatty degeneration. [47][48][49] As shown in Fig. 2G and H, the expression of PERK and CHOP increased remarkably under TBT exposure, and thus we hypothesized that TBT-induced ER stress might be due to the enhancement COX-2 by activating the PERK and CHOP responses.…”
Section: Discussionmentioning
confidence: 99%
“…46 It has been veried that the action of PERK could affect VLDL receptors that are regulators of liver TG and fatty degeneration. [47][48][49] As shown in Fig. 2G and H, the expression of PERK and CHOP increased remarkably under TBT exposure, and thus we hypothesized that TBT-induced ER stress might be due to the enhancement COX-2 by activating the PERK and CHOP responses.…”
Section: Discussionmentioning
confidence: 99%
“…ApoB100 and microsomal TG transfer protein (MTP) mediate VLDL secretion in hepatocytes. Studies have revealed that pharmacological inhibition of MTP can be used to treat hyperlipidaemia in rats with monosodium L-glutamate-induced obesity, while increases in MPT gene or protein expression can be used to treat NAFLD [33][34][35]. Studies have also indicated that upregulating PPAR-α, carnitine palmitoyltransferase-1a (CPT-1a) and fatty TG lipase (ATGL) to enhance FA oxidation and lipolysis can improve NAFLD in micee [36,37].…”
Section: Pathogenesis Of Nafld and Glycolipid Metabolismmentioning
confidence: 99%
“…In mice fed a high-fat diet for 12 weeks, oral administration of PA (25 and 50 mg/kg body weight) decreased the weight of abdominal white adipose tissues (epididymal and retroperitoneal adipose tissue). In a fatty liver animal model using Sprague Dawley rats, oral administration of PA (10, 20 and 40 mg/kg body weight) for four weeks attenuated hepatic steatosis through not only suppressing endoplasmic reticulum (ER) stress by inactivating ER stress mediators (PERK, IRE1 and ATF6) but also regulating hepatic VLDL uptake by reducing VLDL receptor expression and elevating VLDL secretion [29] . These reports imply that PA can be used for the prevention or treatment of metabolic diseases as a dietary supplement or functional food material.…”
Section: Health Beneficial Effects Of Pamentioning
confidence: 99%
“…Diverse health beneficial activities have been documented for PA, including: anti-influenza virus [10] , [11] , [12] , [13] , anti-inflammatory [14] , [15] , [16] , [17] , anti-oxidative [18] , anti-ulcerogenic [19] , [20] , anti-colitis [21] , [22] , anti-mucositis [23] and protective activities against brain and lung injuries [24] , [25] . Most recently, the effects of PA on cancer and metabolic disorders including obesity, fatty liver and gut microbiota have come under investigation [26] , [27] , [28] , [29] . However, despite these diverse beneficial effects, there is a lack of preclinical and clinical studies for the use of PA in the treatment of human diseases.…”
Section: Introductionmentioning
confidence: 99%